محاولات التحريف المعنوي للقرآن الكريم: مفهومه وصوره وأقسامه: دراسة وصفية - السلمي، فهد بن عبدالمنعم بن صقير (جامعة الأندلس للعلوم والتقنية, 2020)
تهدف هذه الدراسة إلى تفصيل معاني التحريف المعنوي للقرآن الكريم ومسمياته عند العلماء واصطلاحاته، وبيان بعض صوره وأقسامه وأشهرها. كما أنها تهدف إلى بيان أسباب التحريف المعنوي، سواء ما كان بالتأويلات الباطلة لمعانيه أو بالتدليس أو الكتمان ونحوها من صور التحريف التي شابهت فيها بعض الفرق الإسلامية ما سارت عليه اليهود والنصارى من طرق ومناهج التحريف للكتب السابقة، وذلك من خلال تحليل النصوص الواردة في وصف تحريف أهل الكتب السابقة لكتبهم وتحذير القرآن الكريم لهذه الأمة من اتباع ذلك. ثم ناقشت هذه الدراسة أنواع التحريف الصوتي وأسبابه وآراء العلماء فيه، ومدى تأثيره في معاني القرآن وأحكامه، ومدى الإثم الواقع على من فعل ذلك من جهال الناس وعامتهم وعلمائهم. كما أنها ناقشت أثر التحريف المعنوي للقرآن الكريم على قوة هذه الأمة وعزتها، وأثره في شق صفها وذهاب ريحها، ودوافع ذلك والمعالجات المفترضة لحل هذا الاختلاف والوقوف في وجه تحريف القرآن بشتى صورة وأقسامه.
The study aims to detail the meanings of semantic distortion of the Holy Quran and its titles and idioms among scholars as well as stating some types and most common divisions. In addition, the study aims to express the reasons for semantic distortion whether through void interpretations, cheating, denial, or other forms of distortion in which some Islamic sects are similar to the Jewish and Christians in distortion methods and means of the previous holy books. The study analyzed the texts describing how the people of previous holy books distorted their books and warning this nation to do so in the Holy Quran. The study discussed types of phonetic distortion, reasons, scholars' opinion about, its effect on the meanings and provisions of the Holy Quran, the sin gained by those who do so of regular and ignorant people and scholars in general and in particular. The study also discussed the effect of semantic distortion of the Holy Quran on the strength of this nation and its dignity as well as its impact on its weakness and reasons for such distortion. It presented the supposed treatment to solve such difference and stand against the Quran distortion with different types and shapes.
Keywords: القرآن الكريم -- معاني القرآن -- التحريف المعنوي للقرآن -- رد الشبهات